The Controversy of Hymenoplasty in Islamic Law and Saddu Al-Dhara’i Perspective for Contextual Learning - Muji; Nurhasan; Rahman, Siti Fatinnah Binti Ab (Journal of Teaching and Learning, 2025)
The medical and social issues surrounding hymenoplasty, a procedure aimed at restoring the hymen, have sparked controversy, particularly within Muslim communities. This practice is often driven by social and aesthetic pressures, with the hymen being viewed as a symbol of a woman's purity and morality. However, the procedure raises complex ethical dilemmas, both medically and socially, that require thorough examination within the context of Islamic law. This study aims to explore the controversy surrounding hymenoplasty from the perspective of Islamic law, with a focus on applying the principle of Saddu Al-Dhara’i as a tool to assess the legitimacy of this practice. The research employs a qualitative approach with a literature review, analyzing relevant texts to explore Islamic viewpoints on the issue. The findings indicate that Islamic law views hymenoplasty as a practice that can lead to misuse, particularly if it is used to conceal behavior contrary to Islamic moral values, such as adultery. Through the principle of Saddu Al-Dhara’i, this procedure can be seen as an action that should be limited in order to prevent greater harm to individuals and society. The study also highlights the importance of integrating this issue into Islamic education to provide a deeper understanding of Sharia values in everyday life. Thus, this research contributes to the formation of a contextual perspective in Islamic education, which combines legal, social, and ethical aspects.